Perlindungan Hukum Tanggung Jawab Pidana Editor Dalam Produk pers - Faris Meode Togatorop; Rizki Rian Perdana2; Ayu Putriyana (GLOBAL SCIENTS PUBLISHER, 2025)
The legal responsibilities and risks faced by an editor in the press industry are enormous. Editors must ensure that the news presented is accurate, balanced, and complies with applicable laws. They risk facing legal action, such as defamation or the dissemination of false information. Therefore, it is important for editors to carry out their duties with professionalism and caution at every stage of the editorial process. In addition to highlighting the responsibilities of editors, this study also emphasizes the need to strengthen legal protections for journalists. This protection, including the implementation of the Right of Reply and the Right of Correction, is crucial to guarantee freedom of expression while protecting individuals' rights from the impact of inaccurate or unfair news.